Biological sensors and bio-inspired technologies: the role of insects in advanced detection systems and robotics - Ebrahim Abbasi (Discover Applied Sciences)
Abstract This study explores the potential of insect-derived sensory systems, bio-inspired robotics, and bio-inspired materials in advancing modern technology. Insects possess highly specialized sensory mechanisms and locomotion strategies that have evolved over millions of years, offering novel insights for the development of bio-electronic sensors, adaptive robots, and innovative materials. The study employs a combination of electrophysiological recordings, computational modeling, and bio-engineering techniques, including microfabrication of bio-sensors, neural interfacing for insect-controlled robotics, and genetic modifications for analyzing insect sensory mechanisms to investigate the sensory capabilities of insects such as honeybees, fruit flies, and cockroaches. The findings reveal that insect olfactory receptors, mechanosensory systems, and locomotion patterns can be effectively mimicked in bio-hybrid robots and bio-inspired materials. These bio-inspired systems demonstrated enhanced chemical detection capabilities, multi-terrain adaptability, and efficient material properties. Furthermore, insect-derived nanostructures were successfully replicated to create superhydrophobic surfaces and energy-efficient photonic materials. This study underscores the vast potential of biomimicry in addressing intricate engineering challenges, including the development of sustainable materials, adaptive robotics, and advanced sensing technologies However, scalability and ethical considerations remain key challenges for the widespread adoption of insect-inspired systems. The integration of AI, computational modeling, and bio-engineering presents a promising pathway toward next-generation technologies.